2021
DOI: 10.1038/s41467-021-25782-2
|View full text |Cite
|
Sign up to set email alerts
|

Near 100% ethene selectivity achieved by tailoring dual active sites to isolate dehydrogenation and oxidation

Abstract: Prohibiting deep oxidation remains a challenging task in oxidative dehydrogenation of light alkane since the targeted alkene is more reactive than parent substrate. Here we tailor dual active sites to isolate dehydrogenation and oxidation instead of homogeneously active sites responsible for these two steps leading to consecutive oxidation of alkene. The introduction of HY zeolite with acid sites, three-dimensional pore structure and supercages gives rise to Ni2+ Lewis acid sites (LAS) and NiO nanoclusters con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…142,143 The careful design and modification of the NiO-based systems by tuning the surface oxygen concentration, addition of Sn, Ti and Nb oxides, or simple variation of NiO concentration can also help to achieve a higher olefin selectivity and a higher productivity. 135,136,144–147 Finally, a technico-economic analysis of the ethane ODH indicates its potential for industrial implementation, competitive with the SC process. 148…”
Section: Light Olefin Synthesis From Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…142,143 The careful design and modification of the NiO-based systems by tuning the surface oxygen concentration, addition of Sn, Ti and Nb oxides, or simple variation of NiO concentration can also help to achieve a higher olefin selectivity and a higher productivity. 135,136,144–147 Finally, a technico-economic analysis of the ethane ODH indicates its potential for industrial implementation, competitive with the SC process. 148…”
Section: Light Olefin Synthesis From Hydrocarbonsmentioning
confidence: 99%
“…The Ni 2+ Lewis acid sites were responsible for dehydrogenation, while the NiO nanoclusters acted as selective hydrogen combustion centers. 144…”
Section: Light Olefin Synthesis From Hydrocarbonsmentioning
confidence: 99%
“…This should stem from active isolated In sites for ethane activation and selective In 2 O 3 nanoparticles in main-group In catalysts induced by the delocalized s-/p-bands as the host orbitals of In, leading to weak re-adsorption of ethene and thus its facile desorption. In contrast, 6Ni/NaY as one of the most reported transition metal oxides for oxidative dehydrogenation of alkanes exhibited only 2% ethene yield because the subtly increased conversion led to a significantly decreased selectivity (Figures c and S27), usually encountered with transition metal oxide catalysts in selective oxidation. This should originate from the narrow d-band of transition metals resulting in strong interaction with ethene in spite of its excellent ability to activate ethane. ,,, 11In/HY with the unprecedented ability to avoid over-oxidation concurrently with high activation for ethane enabled by atomically dispersed In sites achieved the highest ethene yield of nearly 60% and outperformed most catalysts ever reported, including transition metal oxides (Figure e). ,, , We further evaluated the performance of x In/HY for the oxidative dehydrogenation of propane and butane (ODP and ODB), which are also important and challenging reactions for the production of alkenes in the chemical industry. The results showed that the C 3 H 8 and C 4 H 10 conversion of x In/HY were almost one magnitude higher than that of x In/NaY concurrently with high C 3 H 6 and C 4 H 8 selectivity (Figure S28), indicating that the main-group catalyst with atomically dispersed In sites could also exhibit high performance in other oxidative dehydrogenation reactions.…”
Section: Resultsmentioning
confidence: 98%
“…Transition metal oxides with variable oxidation states have been mostly studied due to their excellent ability to adsorb and activate alkanes. Unfortunately, their reduced counterparts with closely spaced and partially occupied d-orbitals strongly interact with reactive functional groups contained in olefins, leading to difficulty in their desorption and thus over-oxidation. ,, To this end, extensive studies have been devoted to manipulating their reactivity to olefins by creating functionalities exemplified by Mo–V–Te–Nb catalysts with a selective M1 phase, increasing the metal–oxygen bond strength such as in doped V-based catalysts, decreasing the number of surface-active but nonselective electrophilic oxygen species such as in doped and supported Ni-based catalysts, preventing the exposure of coordination unsaturated cations by a selective surface shell typically represented by metal oxide-supported alkali metal oxides or chlorides, ,, and tailoring dual active sites to isolate dehydrogenation and oxidization . While the selectivity to olefins was greatly enhanced by manipulating the activity of transition metal oxides from strength to weakness, the conversion decreased concurrently as a result of suppressed adsorption and activation of alkanes, thereby limiting the yield of olefins.…”
Section: Introductionmentioning
confidence: 99%
“…The XPS experiments are performed and shown in Figure . Three peaks of Ni 2p 3/2 are recorded in the BE spectrum, and the main signal at around 856.7 eV is attributed to Ni 2+ cations that interact with the support . Meanwhile, a small signal at 853 eV may belong to surface NiO.…”
Section: Resultsmentioning
confidence: 99%